Jellyfish fishery in Pakistan - Gul, Shahnawaz (2016)
This study reports on the jellyfish (Cnidaria: Scyphozoa) fishery in Pakistan for the first time. Two jellyfish species: Catostylus perezi and Rhopilema hispidum, marketed with the trade names: banana and flower-jellyfish, respectively, are commercially exploited in Pakistan with the former being caught and exported in much higher relative quantities. C. perezi is fished in Balochistan, while R. hispidum is fished in Sindh province. Fishing seasons vary between February/March to July/August and 8–10 companies are regularly processing jellyfish, primarily using the oral arms, their fused-portion and scapulets, while umbrellas are typically not processed. The industry in the region has great potential because C. perezi occurs at high abundances in the northern Arabian Sea along the Balochistan coast of Pakistan.